Functionally Graded Oxide Scale on (Hf,Zr,Ti)B2 Coating with Exceptional Ablation Resistance Induced by Unique Ti Dissolving - Junshuai Lv; Wei Li; Yanqin Fu; Menglin Zhang; Lingxiang Guo; Fanyu Lu; Jiachen Li; Tao Li; Yulei Zhang; Hejun Li (Advanced Science)
Abstract Multicomponent Ti‐containing ultra‐high temperature ceramics (UHTCs) have emerged as more promising ablation‐resistant materials than typical UHTCs for applications above 2000 °C. However, the underlying mechanism of Ti improving the ablation performance is still obscure. Here, (Hf,Zr,Ti)B2 coatings are fabricated by supersonic atmospheric plasma spraying, and the effects of Ti content on the ablation performance under an oxyacetylene flame are investigated. The (Hf0.45Zr0.45Ti0.10)B2 coating shows superior ablation resistance and cycling reliability at ≈2200°C. A functionally graded oxide scale comprising an outer dense layer and an underlying fine granular layer formed. The former is a better oxygen barrier owing to fewer cracks and the latter has high strain tolerance due to finer grain size. The uniform dissolving of ≈4 mol% Ti in the inner layer results in grain refinement via sluggish diffusion and thus stress release. For the outer layer, Ti segregation at the nanoscale leads to a metastable cubic (Hf,Zr,Ti)O2 and local severe lattice distortion, inhibiting the propagation of cracks. Ti ions’ unique dissolving in the oxide scale enables a strong oxygen diffusion barrier with high strain tolerance, which is responsible for superior performance. This study provides new insights into the ablation behavior of Ti‐containing multicomponent UHTCs.